2012
DOI: 10.1177/030006051204000534
|View full text |Cite
|
Sign up to set email alerts
|

A Single-centre, Before-After Study of the Short- and Long-term Efficacy of Narivent® in the Treatment of Nasal Congestion

Abstract: OBJECTIVE: Nasal congestion is a common symptom in allergic and nonallergic rhinitis, rhinosinusitis and nasal polyposis. The present study evaluated the clinical effectiveness of Narivent ® , an osmoticallyacting medical device with antioedematous and anti-inflammatory effects, in nasal congestion. METHODS: A single-centre, prospective study with a prepost design and consecutive patient enrolment was conducted in an Italian otolaryngology department. Patients with persistent nasal congestion were allocated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…1C , we found that, at variance with saline, Narivent and Budesonide equally reduced the HMGB1 content in nasal fluids after 1 week of treatment. Reportedly, GLT is known to inhibit 11p-hydroxysteroid dehydrogenase 2 and to promote arterial hypertension via cortisol accumulation [ 15 ]. However, it is not known whether nasal formulations containing GLT can increase cortisol levels because of systemic absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C , we found that, at variance with saline, Narivent and Budesonide equally reduced the HMGB1 content in nasal fluids after 1 week of treatment. Reportedly, GLT is known to inhibit 11p-hydroxysteroid dehydrogenase 2 and to promote arterial hypertension via cortisol accumulation [ 15 ]. However, it is not known whether nasal formulations containing GLT can increase cortisol levels because of systemic absorption.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, GLT is the sole compound used to inhibit HMGB1 signalling in the clinic due to its anti-inflammatory properties (see http://www.minophagen.co.jp ). In this respect, the nasal formulation Narivent is a recently developed GLT-containing medical device used to treat inflammation of the nasal mucosa [ 15 ]. Therefore, on one hand, the use of GLT-containing formulations may help unravel the pathogenetic role of HMGB1 in rhinitis-related disorders, and on the other hand, it may represent innovative tools for the treatment of upper airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Enoxolone, a potent anti-inflammatory, and immunomodulatory molecule, associated with mannitol, an osmotic anti-oedema agent, have been demonstrated able to improve the nasal mucociliary transport time [143], to reduce nasal eosinophilia in allergic children [144], and significantly reduce the severity of nasal congestion [145,146].…”
Section: Therapeutic Strategies For Ua Diseases Based On Local and Rementioning
confidence: 99%
“…The adoption of milder therapeutic strategies, like Narivent ® , might represent an interesting option in view of its lower adverse reactions rates in front of a proven efficacy [27]. Narivent ® has been shown to have: (i) an antioedematous action, due to the presence of mannitol, a naturally occurring sugar alcohol, widely used in pharmaceutical formulations and food products, and employed therapeutically for its known osmotic action; (ii) an anti-inflammatory action, due to the presence of glycyrrhizin, a glucosidic triterpene extracted from the roots of the liquorice plant, which is the first direct inhibitor of HMGB1 (High-mobility group box 1 protein; intranuclear protein), which acts as a potent pro-inflammatory mediator when released in the extracellular environment; and (iii) as lubricant, due to the presence of copolymer of methyl vinyl ether and maleic anhydride (PVM/MA copolymer), which is classified as a Poly vinyl methyl ether (PVME or PVM).…”
Section: Discussionmentioning
confidence: 99%